HUBUNGAN PERSEPSI BELAJAR DENGAN MOTIVASI BELAJAR MATA PELAJARAN EKONOMI SISWA SMA SANTUN UNTAN PONTIANAK - Elfira, Elsa; Warneri, Warneri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the relationship of perceptions of learning economic subjects with motivation to learn economic subjects of students of class X MIA SMA Santun Untan Pontianak. The research method used is descriptive with the form of quantitative research. The source of this research data is the students of class X MIA and the data is the answer sheets questionnaire students class X MIA. The results showed the perception of learning economic subjects with absorbent percentage (52.27%), understanding or understanding (47.27%), assessing or evaluating (46.59%), including into the less favorable category. motivation to study economic subjects of class X MIA students with percentage of desire and desire succeed (43,94%), existence of motivation and requirement in learning (56,8%), existence expectation and future aspiration (48,49%) (50%), learning activities (50%), conducive learning environment (36.36%) are not good enough. the correlation between the perception of learning of economic subjects with the motivation to study the economic subjects of the class X MIA students is obtained tcount of 9,321, when compared with the ttable of 5% significance level equal to 2,068 then thitung> ttable (9,321> 2,068) Ha is accepted. The magnitude of the relationship of perceptions of learning economic subjects with the motivation to learn economic subjects of class X students MIA obtained by 0.900 including a very strong category.Â Keywords: Perception Of Studying, Economics Subjects, Â Motivation Of Studying